Psychological readiness of students to work in a professional field - UHRYN, OLHA (Journal of Education Culture and Society, 2020)
The article is devoted to the psychological readiness of student’s personality for profes-sional life. The author considers components of readiness that promote self-development and self-realisation in the professional sphere, and presents the results of an empirical stu-dy of willingness to work in a professional field.